Short Communication: Diversity of sponges associated in seagrass meadows at coastal area of Pacitan District, East Java, Indonesia - EDWIN SETIAWAN; MOHAMMAD RIZKI CHODIANTORO; GHULAM FATHUR INSANY; IWENDA BELA SUBAGIO; NURUL KUSUMA DEWI; FARID KAMAL MUZAKI (Society for Indonesian Biodiversity, 2021)
Abstract. Setiawan E, Chodiantoro MR, Insany GF, Subagio IB, Dewi NK, Muzaki FK. 2021. Short Communication: Diversity of sponges associated in seagrass meadows at coastal area of Pacitan District, East Java, Indonesia. Biodiversitas 22: 3105-3112. Sponges are sessile organisms and aquatic filter feeders that play an important role in marine ecosystems. They are also secondary metabolite compounds that exhibit promising novel properties. Indonesia has been categorized as a hot spot for sponge diversity. Despite this fact, some Indonesian coastal areas, especially in the southern area of East Java, have not yet been comprehensively explored to understand its diversity and potential value. For this reason, we investigated species richness of sponges associated with seagrass meadows in the southern coastal area of Pacitan District, in East Java. Seagrass meadows are important coastal areas that have been recognized as buffer zones for sustainable marine conservation because it provides safe shelter and acts as a nursery for many fishes and other invertebrates, including sponges. We identified 16 genera out of 12 families from two selected beaches in Pacitan. Boring sponges belonging to the Clionaidea family were dominant in those areas, covering more than 20 percent of the total recorded specimens. Moreover, conspicuous boring sponges in this study can be used for further environment alert since this group plays a vital role and negatively impacts destroying the calcium carbonate of marine organisms.